The determinants of hedging and firm value: an empirical study in mining companies listed on Indonesia stock exchange - Irawanti, Garnis; Moeljadi, Moeljadi; Indrawati, Nur Khusniyah (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
This study aims to determine the determinant factors in the company's hedging decisions and to determine whether the activities of corporate hedging decisions through derivative instruments provide increased value for the company. The sample consisted of 33 mining companies listed on Indonesia Stock Exchange during 2011-2015 period. The method used in this study is logistic regression and independent sample t-test. The result of logistic regression by using variable of financial distress, underinvestment cost, and size showed a positive correlation to corporate hedging decision. Meanwhile, by using an independent sample t-test found that the company's hedging decisions significantly affect the value of firms and the companies with hedging decision activity through derivative instruments have more superior value than companies by using natural hedging decisions.Â